The Nature and Object of the History of the Kasunanan Giri Kedaton: An Analysis of Political Stability in 1481-1605 AD - Sirojuddin, Ahmad; DH, Achmad Zuhdi, (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to reconstruct the political stability of Giri Kedaton by combining a philosophical examination of the nature and scope of historical research. The primary focus of this study lies in analysing the leadership of those bearing the title ‘Sunan Giri’, covering the periods of Raden Paku, Raden Ali Sumodiro, Pangeran Wiro Kesumo, and the golden age under Raden Fatikhal. Using critical historical methods, including heuristics, source verification, interpretation, and historiography. This study reveals that the internal stability maintained for over a century stemmed from the institutionalisation of dual legitimacy. The research findings indicate that although Giri Kedaton frequently faced external military threats (such as the Sengguruh attack and pressure from Islamic Mataram), the relatively conflict-free internal succession process demonstrated the robustness of the dual legitimisation institutionalised by the rulers of Giri. The scope of this study confirms that the pattern of symbolic leadership was a determining factor in the political resilience of Giri Kedaton amidst the dynamics of power transition in Java.